Assessment of Lean-Green Integration Throughout Manufacturing Transportation Activities - Abdullah, Prof. Zuher Hassan; Dawood, Prof.Dr. Lamyaa Mohammed (University of Thi-Qar Journal, 2019)
This aims of this research is to study the effect of all transportation activities through lean and green management perspective. AL-Kufa /Iraq Cement plant is considered as a case study to examine the effect of individual and overall results that may contribute in the lean-green integration. Life cycle assessment was used as an environmental key performance indicator for lean green integration. Relationship matrix, Pie, and Pareto charts were tools and techniques used to assess the present results. Results were generated using Minitab Version 17 and Edraw Max. Version 7 software. Results showed that the material transported throughout processing was crucial in effecting on lean green integration not the transportation media. Since the same transportation media could be, synergistic, or conflicting according to position of this media to the process and relative material type transported. Results also show that transportation activities, throughout grinding resulted particulate matters that causes winter smog environmental impact. Thus human health impairments (Hi) damage in this transportation activity resulted 42.94 %. Followed by kiln production and cooling by 25 %. The rest value was divided between packaging, and finish grinding processes.